The Interaction Effect of Heuristic Representation on Initial Public Offering Anomaly: Evidence from Flipping Activity - Hon-Wei Leow; Wee-Yeap Lau (Australasian Accounting, Business and Finance Journal, 2020)
This study examines the impact of the heuristic representation on IPO anomaly in the context of an emerging market from January 2006 to December 2016. Models consist of multiple regression has been evaluated. Our results show: firstly, the distribution of initial return, oversubscription ratio, firm age, offer period, firm size, heuristic representation, and flipping activity are positively skewed; Secondly, the oversubscription ratio has a positive relationship with flipping activity. This is because higher demand makes investors flip more to liquidate the IPO on the first trading day. In contrast, firm size has a negative relationship with flipping activity. A larger IPO firm is more stable in terms of performance, and less risky in terms of business operation; Thirdly, heuristic representation influences the relationship between oversubscription ratio and flipping activity; Lastly, this study dispels the notion that investors are active in subsequent trading but not necessarily obtain a profit from the liquidation. This study extends earlier work by examining the interaction effect of heuristic representation to the flipping activity in an emerging market.
Keywords: Heuristic representation; IPO anomaly; Initial return; Oversubscription ratio; Firm size; Flipping activity